The histone deacetylase inhibitor Suberoylanilide Hydroxamic Acid (SAHA) as a therapeutic agent in rhabdomyosarcoma. Issue 3 (4th March 2019) - Ghayad, Sandra E.; Rammal, Ghina; Sarkis, Omar; Basma, Hussein; Ghamloush, Farah; Fahs, Assil; Karam, Mia; Harajli, Mohamad; Rabeh, Wissam; Mouawad, Joe E.; Zalzali, Hassan; Saab, Raya
ABSTRACT: Rhabdomyosarcoma (RMS) is an aggressive childhood sarcoma with two distinct subtypes, embryonal (ERMS) and alveolar (ARMS) histologies. More effective treatment is needed to improve outcomes, beyond conventional cytotoxic chemotherapy. The pan-histone deacetylase inhibitor, Suberoylanilide Hydroxamic Acid (SAHA), has shown promising efficacy in limited preclinical studies. We used a panel of human ERMS and ARMS cell lines and xenografts to evaluate the effects of SAHA as a therapeutic agent in both RMS subtypes. SAHA decreased cell viability by inhibiting S-phase progression in all cell lines tested, and induced apoptosis in all but one cell line. Molecularly, SAHA-treated cells showed activation of a DNA damage response, induction of the cell cycle inhibitors p21 Cip1 and p27 Kip1 and downregulation of Cyclin D1. In a subset of RMS cell lines, SAHA promoted features of cellular senescence and myogenic differentiation. Interestingly, SAHA treatment profoundly decreased protein levels of the driver fusion oncoprotein PAX3-FOXO1 in ARMS cells at a post-translational level. In vivo, SAHA-treated xenografts showed increased histone acetylation and induction of a DNA damage response, along with variable upregulation of p21 Cip1 and p27 Kip1 . However, while the ARMS Rh41 xenograft tumor growth was significantly inhibited, there was no significant inhibition of the ERMS tumor xenograft RD. Thus, our work shows that, while SAHA is effective against ERMS and ARMS tumor cells in vitro, it has divergent in vivo effects . Together with the observed effects on the PAX3-FOXO1 fusion protein, these data suggest SAHA as a possible therapeutic agent for clinical testing in patients with fusion protein-positive RMS.